MENGANALISIS PENERAPAN NILAI SALAF DALAM BUDAYA LITERASI SEBAGAI MODEL KETELADANAN SISWA SMP ISLAMIC CENTER BIN BAZ DI PERPUSTAKAAN - Nuryadin, Nuryadin; Buton, La Mislan; Zaid, Zaid; Rumata, Teguh Pratama Syahmal Ramadhana R; Suhail, Fikri Ahmad; Fajrin, Muh; Pahlevi, Riza; Hafiz, Khairil; Fitrianto, Ibnu (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the implementation of Salaf values in literacy culture as a model of student character formation at SMP Islamic Center Bin Baz. The research stems from academic concern over the shifting meaning of literacy in Islamic educational institutions, which often emphasizes technical reading and writing skills while neglecting their moral and spiritual dimensions. Employing a descriptive qualitative approach with a single case study design, data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that Salaf values such as sincerity (ikhlas), humility (tawadhu’), discipline, and ethical learning (adab sebelum ilmu) are effectively integrated into literacy activities through programs like “Tahsin and Tadabbur Buku” and “Majlis Qira’ah.” These practices significantly enhance students’ reading discipline, ethical conduct, and spiritual awareness. The library functions as a moral and intellectual space that cultivates exemplary behavior among students. The study concludes that literacy based on Salaf values represents a new paradigm in modern Islamic education, bridging intellectual development with moral and spiritual integrity. This research contributes a conceptual framework for developing a holistic and applicable model of religious literacy in Islamic educational settings.